Mrs. Noah's vegetable ark - Pasquali, Elena; Lavis, Steve (Oxford : Lion Children's, 2011)
Mrs. Noah sets out to save her vegetable garden from the coming flood with the help of some resourceful animals.
Booklist
Booklist, April 2011
3.5
K-3
K-3
Keywords: Environmentalism -- Juvenile fiction; Gardening -- Juvenile fiction; Noah's ark -- Juvenile fiction; Vegetables -- Juvenile fiction; Environmentalism -- Fiction; Gardening -- Fiction; Noah's ark -- Fiction; Vegetables -- Fiction; Environmental protection -- Fiction; Gardening -- Fiction; Noah's ark -- Fiction; Vegetables -- Fiction; Picture books for children